Calculus with applications - Lial, Margaret L.; Greenwell, Raymond N.; Ritchey, Nathan P. (Pearson Education Limited, 2017)
Calculus with Applications, Eleventh Edition by Lial, Greenwell, and Ritchey, is our most applied text to date, making the math relevant and accessible for students of business, life science, and social sciences. Current applications, many using real data, are incorporated in numerous forms throughout the book, preparing students for success in their professional careers. With this edition, students will find new ways to help them learn the material, such as Warm-Up Exercises and added "help text" within examples.